IMPLEMENTASI TEKNIK EMBOUCHURE DAN LATIHAN LONG TONE TERHADAP PEMBENTUKAN INTONASI PERMAINAN SAXOPHONE ALTO DALAM IBADAH GEREJA OLEH SISWA KELAS XI SMA NEGERI 2 LINTONGNIHUTA PADA KEGIATAN EVANGELISASI MINGGUAN - Ivanri Tampubolon; Rowilsom Nadeak; Roy Josep M Hutagalung; Testi Bazarni Zebua; Rhyky Renhard D Sihombing (Smart Education, 2026)
Abstract: This study aims to determine and describe the implementation of embouchure techniques and longtone exercises in improving the alto saxophone playing ability of class XI students of SMA Negeri 2 Lintongnihuta. Embouchure technique, which is a coordinated mouth position that involves the lips, facial muscles, jaw, teeth, and chin to support the mouthpiece and reed vibration, so that the resulting tone is correct. Longtone exercises, which are exercises by holding one long note that is actively processed to improve stable intonation and breathing control. The problem in this study is that class XI students of SMA Negeri 2 Lintongnihuta who play alto saxophone still have difficulty in maintaining proper and clear intonation on each note played and the results achieved after implementing the technique. This study explains the practice process and the stages of implementing the technique to improve the ability to play the alto saxophone in accompanying the song